Dictyoceratida (Porifera: Demospongiae) from Tropical Southwestern Atlantic (Northeastern Brazil, Sergipe State) and the description of three new species - Sandes, Joana; Pinheiro, Ulisses (Zootaxa, 2014)
Five species of dictyoceratid sponges were collected from trawling on the continental shelf of Sergipe State, Northeastern Brazil, of which three are new to science: Ircinia sergipana sp. nov., Ircinia repens sp. nov., Ircinia strobilina, Hyattella cavernosa and Smenospongia ramosa sp. nov., the latter the first record of the genus Smenospongia from Brazil.